PENDAMPINGAN INOVASI USAHA KERUPUK TULANG PADA UMKM BERBASIS IKAN DI KABUPATEN OKU - Fifian Permata Sari; Munajat Munajat; Anggi Fatmayati (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2023)
There are many processed fish products which are a source of income for MSMEs, especially those living in areas around the river, such as MSMEs spread across OKU Regency, South Sumatra. Processed products such as kemplang crackers, pempek and fish floss are the main products produced by many MSMEs. Fish bones are a product of processed waste that is mostly wasted, even though it still contains a lot of calcium and protein which is not only found in the fish meat, but also in the bones. Utilizing fish bones into foods such as crackers and kemplang can of course increase the income of MSMEs. The remaining fish bones must of course undergo several treatments before being processed. The idea to process fish bones into a new processed food ingredient, namely fish bone crackers, can actually bring benefits and provide added value for fish-based MSMEs. The texture of fish bone crackers remains tasty and crunchy, with almost no difference from the texture of other crackers, in fact many people don't think that the main ingredient in making crackers is processed leftover fish bones. This service activity was carried out at fish-based MSMEs in OKU Regency with the raw material being fish bones left over from processed crackers which were then reused to be processed into fish bone crackers.